Digitization in commercial banking – is it truly a step forward? : - Meloun, Tomáš (2023)
The emergence of the fourth industrial revolution led to questions surrounding the adoption of novel technologies in various industries, including the banking sector. This thesis aims to examine the rationale for digitizing banks while acknowledging the potential pitfalls of blindly adopting new technologies. In this thesis, the author goes beyond buzzwords to provide a comprehensive analysis of the true potential and practical implications of implementing such technologies in banking. To remain objective and relevant, the author conducted interviews with experts with firsthand experience and knowledge in the banking and IT sectors. These are supplemented by relevant industry reports, journals, articles, and other expert opinions. Through this rigorous synthesis of primary and secondary research, the author evaluates the practicality and implications and offers a forward-looking perspective on the likely future development of these trends. Ultimately, this thesis provides a holistic understanding of the new landscape these technologies bring, emphasizing the need for well-informed decision-making to maximize the benefits and mitigate the risks associated with adopting these technologies.